Analysis Of Engine Radiator Performance At Different Coolant Concentrations And Radiator Materials - Habeeb, Hiyam Adil; Mohan, Ahmed Esmael; Mohamad Norani, Nor Ayu; Abdullah, Mohd Azman; Harun, Mohd Hanif (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Abstract: Functioning as a cooling system, a radiator is an essential component in reducing the temperature of an internal combustion engine (ICE) of a vehicle by absorbing the heat and dissipated it into the air. With good and effective radiator, the engine will perform at optimized condition. In this study, the performance of radiator was analyzed at different radiator materials and coolant concentrations. A spark ignition (SI) 1.5L engine radiator system was used at 20%, 30%, 40%, 50% and 60% ethylene glycol coolant concentrations. The simulation of heat transfer was performed on different fins material, aluminum, brass and copper using commercial available finite element analysis (FEA) software. Promising results showed that, copper fins was the best among the materials. It is also observed that the lower the coolant concentration, the better the performance of the radiator in reducing the ICE temperature.